Bactericidal Activity of Lipid-Shelled Nitric Oxide-Loaded Microbubbles - Maxime Lafond; Himanshu Shekhar; Warunya Panmanee; Sydney D. Collins; Arunkumar Palaniappan; Cameron T. McDaniel; Daniel J. Hassett; Christy K. Holland; Christy K. Holland (Frontiers Media S.A., 2020)
The global pandemic of antibiotic resistance is an ever-burgeoning public health challenge, motivating the development of adjunct bactericidal therapies. Nitric oxide (NO) is a potent bioactive gas that induces a variety of therapeutic effects, including bactericidal and biofilm dispersion properties. The short half-life, high reactivity, and rapid diffusivity of NO make therapeutic delivery challenging. The goal of this work was to characterize NO-loaded microbubbles (MB) stabilized with a lipid shell and to assess the feasibility of antibacterial therapy in vitro. MB were loaded with either NO alone (NO-MB) or with NO and octafluoropropane (NO-OFP-MB) (9:1 v/v and 1:1 v/v). The size distribution and acoustic attenuation coefficient of NO-MB and NO-OFP-MB were measured. Ultrasound-triggered release of the encapsulated gas payload was demonstrated with 3-MHz pulsed Doppler ultrasound. An amperometric microelectrode sensor was used to measure NO concentration released from the MB and compared to an NO-OFP-saturated solution. The effect of NO delivery on the viability of planktonic (free living) Staphylococcus aureus (SA) USA 300, a methicillin-resistant strain, was evaluated in a 96 well-plate format. The co-encapsulation of NO with OFP increased the total volume and attenuation coefficient of MB. The NO-OFP-MB were destroyed with a clinical ultrasound scanner with an output of 2.48 MPa peak negative pressure (in situ MI of 1.34) but maintained their echogenicity when exposed to 0.02 MPa peak negative pressure (in situ MI of 0.01. The NO dose in NO-MB and NO-OFP-MB was more than 2-fold higher than the NO-OFP-saturated solution. Delivery of NO-OFP-MB increased bactericidal efficacy compared to the NO-OFP-saturated solution or air and OFP-loaded MB. These results suggest that encapsulation of NO with OFP in lipid-shelled MB enhances payload delivery. Furthermore, these studies demonstrate the feasibility and limitations of NO-OFP-MB for antibacterial applications.